TAX AGGRESSIVENESS IS SEEN FROM THE CURRENT RATIO, RETURN ON ASSETS, DEBT TO ASSET RATIO, AND CAPITAL INTENSITY IN THE COMPANY IN THE TOURISM, RESTAURANT AND HOTEL INDUSTRY - Supriono (This journal is published by the Vocational School of Universitas Sebelas Maret., 2024)
COVID-19 greatly affected the company's financial condition during 2018-2021, having an impact on the creation of huge losses that it tends to cause several factors to carry out tax aggressiveness, especially among companies listed on the Indonesia Stock Exchange (IDX). Tax aggressiveness or reducing the company's profit income to minimize the tax burden to avoid bankruptcy or maintaining company glory. The purpose of this study is to determine the factors that influence tax aggressiveness from independent variables in the form of the current ratio, return on assets, debt-to-asset ratio, and capital intensity.Quantitative data is used in this study, including data on companies listed on the IDX for the period 2018-2021, including companies in the tourism, restaurant, and hotel industries listed on the IDX during 2018-2021. A total of 108 data or companies from 27 companies became research samples, through the purposive sampling method and using research analysis tools in the form of description analysis, classical assumption test, and hypothesis testing.This study partially shows the results of the current ratio variable have a positive effect, return on assets has a negative effect, debt to asset ratio and capital intensity do not effect on tax aggressiveness during 2018-2021. The current ratio variable, return on assets, debt to asset ratio and capital intensity simultaneously affect tax aggressiveness.